Procurement Ethics and Corruption: An Examination of Italy and Zimbabwe - Mutasa, Vimbai (Global Journal of Purchasing and Procurement Management, 2024)
Purpose: The aim of the study was to analyze the procurement ethics and corruption: an examination of Italy and Zimbabwe. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study on procurement ethics and corruption in Italy and Zimbabwe reveals significant contrasts between the two countries. In Italy, procurement processes are more structured, with stringent regulations aimed at curbing corruption, yet challenges persist, particularly in the enforcement of these regulations. In contrast, Zimbabwe faces more profound issues with systemic corruption deeply embedded in its procurement practices, exacerbated by weaker institutional frameworks and lack of transparency. Unique Contribution to Theory, Practice and Policy: Principal-agent theory, institutional theory & ethical decision-making theory may be used to anchor future studies on analyze the procurement ethics and corruption: an examination of Italy and Zimbabwe. Organizations in both Italy and Zimbabwe should implement robust ethical training programs for procurement officials to promote integrity and accountability. Policymakers in Italy and Zimbabwe should collaborate to develop comprehensive anti-corruption frameworks that address the unique challenges faced in each country’s procurement landscape.